Hepatitis B Core IgM antibody (anti-HBcIgM) among Hepatitis B Surface antigen (HBsAg) negative blood donors in Nigeria (2011)
Background: Transfusion associated Hepatitis B virus (TAHBV) continues to be a major problem despite mandatory screening for Hepatitis B surface Antigen (HBsAg). Presence of HBsAg is the common method for detecting hepatitis B infection. Unfortunately, this marker is not detected during the window period of the infection. Nigeria being a developing country cannot afford DNA testing of all collected units of blood which serve as the only possibility of achieving zero risk of transfusion associated HBV. Five different serological makers of hepatitis B virus (HBV) infection were therefore assessed to evaluate the reliability of using HBsAg marker alone in diagnosis of HBV infection among blood donors and to detect the serological evidence of the infection at the window period. This will preclude the possibility of transmitting hepatitis B through transfusion of Hepatitis B surface antigen (HBsAg) negative blood in Nigeria. Methods: Between July and August 2009, 92 blood donors were enrolled for the study. The prevalence of 5 different markers of Hepatitis B virus infection was detected using Enzyme Linked Immunosorbent Assay (ELISA). Demographic factors were assessed during the study.Results: HBsAg and its antibody (anti-HBs) was detected in 18 (19.6%) and 14(15.2%) of the 92 blood donors respectively. Anti-HBc IgM was found in 12(13.0%) of the 92 blood donors while Hepatitis B envelope antigen (HBeAg) and its antibody (anti-HBe) were detected in 4(8.9%) and 12(26.7%) respectively from 45 donors sampled. HBeAg is a marker of high infectivity and appears after HBsAg. At least one serological marker was detected in 30(32.6%) of the blood donors. Five (5.4%) of the 92 donors had anti-HBc IgM as the only serological evidence of hepatitis B virus infection. Conclusions: The result of this study shows that five donors have anti-HBcIgM as the only serological evidence of HBV infection. Inclusion of anti-HBcIgM in routine screening of blood donors in Nigeria should be encouraged. This is the first study to assess anti-HBcIgM in the country.